Impact of Embankment Construction on Sedimentation and Ecosystems in the Ajoy River Basin - Hasibur Rahaman Molla (Research Advances in Environment, Geography and Earth Science Vol. 9, 2024)
Embankment construction along rivers is a common practice for flood control and irrigation purposes. However, it can significantly alter the natural flow of water and sediment transport within the river basin. This study investigates the impact of embankment construction on sedimentation patterns and ecological health in the Ajoy River Basin, India. Embankment is supposed to be an important structural measure of flood control. The performance of embankment varies from case to case. It is quite effective for short term flood alleviation, but it put a question so far as the long-term viability of the embankment is concerned and become harmful to the adjacent floodplain. Morphology of the river as well as the micro-topography of the floodplain undergoes great changes as a result of confinement of river flow due to construction of embankment. Cross-sectional surveys at selected locations will be carried out to quantify changes in channel depth, width and overall river morphology due to flow confinement by embankments. The present study is aimed to find out the efficacy of embankment as a flood control measure and to find out the extent of changes in the micro-topography caused by Ajoy embankment. It also evaluates the changes in river morphology, including channel geometry and floodplain micro-topography, resulting from embankment construction.